Caring for Aging Buildings: A Contextual Study of Adaptive Reuse in Aotearoa - de Buyzer (McDermott), Jakob (Auckland University of Technology, 2023)
Protecting buildings of historic significance is a means of ensuring the stories of the past are preserved through the built environment. In a healthcare facility, the significance not only lies in the date of construction and architectural form, but in the care given to patients within the confines of the building. Additionally, the practice of renovating buildings in lieu of demolition has potentially large environmental savings, something all architects today should be conscious of. Adaptive reuse is the process of renovating or reimagining an existing building for a purpose other than what it was originally designed or built. For buildings of historic significance, the process is a balance between conservation and appropriate interventions. This research proposes the application of adaptive reuse alongside other explored architectural ideologies to a protected healthcare building in Auckland, New Zealand. The resulting proposition provides a multi-purpose community area appropriate for the building which was designed in an era when hospital wards maximised natural ventilation and light. This work hopes to celebrate and build on the social legacy of a redundant healthcare building. The design research supports the idea that we should value our built environment more deeply in terms of energy spent and history made. From this ethic of celebratory adaptive reuse the act of demolition is counter intuitive.